2019
DOI: 10.2174/1573402114666181112141953
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Uric Acid as a Predictor of Severity of Hypertensive Disorders of Pregnancy: A Prospective Cohort Study

Abstract: Objective: To assess the relationship between maternal serum uric acid and severity of Hypertensive disorders of pregnancy in a rural tertiary care centre. Materials and Methods: Present study was conducted in Obstetrics and Gynaecology department of rural tertiary care centre of Northern India over seven months (October 2016-May 2017) on 110 women admitted with a Hypertensive disorder of pregnancy (Gestational hypertension, Preeclampsia, Eclampsia) at ≥;34 weeks gestation. Maternal serum uric acid levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…The results concluded that serum uric acid can predict the mode of delivery (normal vaginal or cesarean) among cases of severe pre-eclampsia. These results were corroborated by another study by Kumar et al (2019) [ 36 ], where a significant difference was observed among cases who underwent normal vaginal delivery and cesarean section. In the study by Padma et al (2015) [ 37 ], high serum uric acid levels were associated with delivery by cesarean section.…”
Section: Discussionsupporting
confidence: 82%
“…The results concluded that serum uric acid can predict the mode of delivery (normal vaginal or cesarean) among cases of severe pre-eclampsia. These results were corroborated by another study by Kumar et al (2019) [ 36 ], where a significant difference was observed among cases who underwent normal vaginal delivery and cesarean section. In the study by Padma et al (2015) [ 37 ], high serum uric acid levels were associated with delivery by cesarean section.…”
Section: Discussionsupporting
confidence: 82%
“…Pre-eclampsia accounts for 10-15% of all the maternal deaths occurring worldwide. The most common reason for such high maternal and fetal morbidity and mortality is the unavailability of precise and specific test that can iden fy 12 pregnant women at risk of developing pre-eclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that with the increase in maternal uric acid level, fetal and maternal complications also increases. [7,8] Several studies have shown that with the increase in maternal serum uric acid level, there is an increased risk of fetal complications. In this study, there were 8 cases of IUGR, 4 cases of IUFD and 4 cases of prematurity in women with serum uric acid levels< 5.5mg/dl, whereas there were 7 IUGR, 4 IUFD and 10 prematurity cases in women with serum uric acid level ≥ 5.5mg/dl.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several studies have been done to correlate its severity with the feto-maternal outcome. [7,8,9] Rajalaxmi et al have reported a threshold value of the uric acid level of 5.5mg/dl in women with preeclampsia with the adverse feto-maternal outcome. Around 68% of women with serum uric acid more than 5.5mg/dl were associated with preterm delivery and birth weight less than 2.5kg.…”
Section: Introductionmentioning
confidence: 99%